Pemberdayaan Media Pemasaran Bagi Kelompok UKM Sagulung Kota Batam - Evan Rosiska; Dian Lestari Siregar; Raymond Raymond; Anggia Dasa Putri (LPPM Universitas Putera Batam, 2022)
The Sagulung UKM group is a group of craftsmen and traders located in the Sagulungs Village, Batam City. Problems faced by the Cemara SME Group such as the low understanding of the Cemara UKM Group regarding marketing media, these problems have an impact on the low level of product sales, low productivity and business development of the fir road SMEs where the results of this community service activity have an impact on increasing expertise and skills through mentoring in marketing products and increasing understanding in the use of information technology so as to support sales activities for the SME group in Sagulung Batam City